Modernizing women gender and social change in the Middle East - Moghadam, Valentine M. 1952- (Lynne Rienner, 2003)
Moghadam's influential study of gender dynamics and social processes in the Middle East has been fully updated to reflect a decade of major changes - including shifts in development strategy and population policy, the rise of a reform movement in Iran incorporating both Islamic and secular feminists, and the rise and fall of the Taliban in Afghanistan. New data and analysis of emerging trends make this second edition a welcome successor.